We rule the world: an emerging global class fraction?. Issue 2 (13th April 2015) - Dennis R. Morgan, Prof.; Murray, Georgina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate who rules the world. The hypothesis is that it is the 0.1 per cent of owners and controllers of capital. Design/methodology/approach – This study used secondary sources including the Bureau Van Dyk and The World Top Incomes database to look at distributions of income and wealth (stock ownership). This is supplemented with a secondary source analysis and with some interviews. Findings – The top point one per centers, the wealthy, those on the top incomes and transnational capitalist class are all distinct but overlapping categories that describe the (white) men and (few) women who hold power through their ownership and/or control of capital and who are thereby directly or indirectly able to act hegemonically on an emerging global basis. Research limitations/implications – Theorists of the global school of capitalism Alveredo et al., 2013 argue that there has been a qualitatively new twenty-first century transnational capitalism in the process of emerging (see Robinson, 2012a). This paper tests this assumption and relates it to the work by Hamm 2010. Social implications – The flip side of this progressively widening concentration of income and wealth into fewer (0.1 per cent) hands brings new lows to the polarisation of class, exploitation and domination. All of these have intensified since the 1980s with the end of the Keynesian Compromise. This north/south accentuated division has implications for social justice. Originality/value – This seeks to identify empirical evidence to support the theory of an emerging transnational capitalist class.